2022
DOI: 10.1186/s12879-022-07174-z
|View full text |Cite
|
Sign up to set email alerts
|

Newly arrived Asian-born gay men in Australia: exploring men’s HIV knowledge, attitudes, prevention strategies and facilitators toward safer sexual practices

Abstract: Background Asian-born gay, bisexual and other men who have sex with men (gbMSM) newly arrived in Australia are more than four times as likely than their Australian-born counterparts to be diagnosed with incident HIV. Our aim was to explore experiences of Asian-born gbMSM newly arrived in Australia and attending a sexual health centre with regards to their knowledge of and preference for HIV prevention strategies. Results Twenty-four gbMSM aged 20–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We found that recently arrived GBM were more likely than nonrecently arrived GBM to be younger, born in Europe, Central or South America and be students. Recently arrived GBM had lower levels of awareness and use of PrEP, echoing pre-vious Australian research [6,8,19], and reported similar levels of casual sex with a risk of HIV acquisition to longerterm residents. Recently arrived migrants were less likely to report HIV testing at services that may incur a cost, like GPs.…”
Section: Discussionmentioning
confidence: 79%
“…We found that recently arrived GBM were more likely than nonrecently arrived GBM to be younger, born in Europe, Central or South America and be students. Recently arrived GBM had lower levels of awareness and use of PrEP, echoing pre-vious Australian research [6,8,19], and reported similar levels of casual sex with a risk of HIV acquisition to longerterm residents. Recently arrived migrants were less likely to report HIV testing at services that may incur a cost, like GPs.…”
Section: Discussionmentioning
confidence: 79%
“…A lack of Medicare coverage has also been independently associated with not using PrEP despite a willingness to use it ( 36 ). Qualitative research from 24 newly-arrived Asian-born MSM reported significant barriers including shame, stigma and fear related to HIV and their sexual identity remained despite living in a more liberal society ( 17 , 18 ). More implementation research is needed to understand how to address the barriers of newly arrived Asian-born MSM to using effective HIV prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For the formative step of the DCE, we conducted semi-structured in-depth interviews with 24 newly-arrived Asian-born MSM between May to December 2019 to understand their experience of HIV testing and type of prevention strategies ( 17 , 18 ). We found most men relied on condoms for HIV prevention but many indicated an interest in accessing PrEP.…”
Section: Methodsmentioning
confidence: 99%
“…34,35 Overseas-born (particularly Asian-born) GBM may face additional challenges in negotiating PrEP use and HIV prevention due to a lack of knowledge about HIV, racism, and lack of access to Medicare (Australia's subsidised health insurance system). [36][37][38] Further research may be warranted to understand how disclosure and discussion of PrEP use, and the use of other HIV risk reduction strategies, evolves as PrEP use increases and the COVID-19 pandemic impacts on sexual behaviour among GBM.…”
Section: Discussionmentioning
confidence: 99%